Tales of the Alhambra: Women's programs as harems. - Elizabeth Carriere (Adult Education Research Conference, 1996)
This study illustrates how women’s programs in governments and institutions can be co-opted by bureaucratic operations. It utilizes feminist critiques of bureaucracy to describe how women’s programs and workers are feminized within the zones they occupy in organizations: exoticized as experts on, and inhabitants in, their own oppressive enclosures; and quarantined as/in "women’s places" within the bureaucracy.